Digital remains: property or privacy?. (22nd November 2022) - Birnhack, Michael; Morse, Tal
Abstract: How should the law treat digital remains, namely, digital personal information of deceased people? Two rival conceptions compete over the best framing: property and privacy. Under property framing, digital remains are just another form of assets, subject to succession law; under privacy framing, digital remains are personal data, and upon death, are not part of the estate. However, whether privacy rights survive death is contested. This article distinguishes between four legal categories of digital remains (intangible items, information about property, intellectual property and personal data), unpacks the two rival framings, and argues that the property framework captures the first three categories of digital remains, but not the last. The article examines the argument for posthumous privacy and concludes that at most, the law should protect reasonable expectations of the living regarding their post-mortem condition, subject to balancing them with competing interests and rights of the living.